Black nightshades, Solanum nigrum L. and related species - Edmonds, J.M.; Chweya, J.A.; Leibniz Institute of Plant Genetics and Crop Plant Research (1997)
The black nightshades (Solanum nigrum and related species in sect. Solanum) are worldwide weeds of arable land, gardens, rubbish tips, soils rich in nitrogen, in moderately light and warm situations which occur from sea to montane levels. They are, however, also widely used as leafy herbs and vegetables, as a source of fruit and for various medicinal purposes. Therefore, human consumption of their leaves and fruits as food is widespread, particularly in Africa and SE Asia. Unfortunately, there is widespread confusion over the precise identification of the taxa involved, especially in those areas in which the species are most commonly used as food sources. This monograph attempts to identify the species related to the black nightshade more accurately, by providing an identification key, descriptions of the taxa most widely reported to be of dietary and/or ethnobotanical use in various Asian, African and Indonesian countries, listing some of the many vernacular names used for the species, recording precise uses of the various species and presenting some information on their genetic resources. Two appendices are included listing (1) research contacts and centres of research, and (2) gene banks maintaining collections. (Abstract © CAB ABSTRACTS, CAB International)